STRUGGLE FOR BETTER LIFE IN RON HOWARD'S CINDERELLA MAN MOVIE:AN INDIVIDUAL PSYCHOLOGICAL APPROACH - WATY, SHINTA DEVITA (2011)
The purposes of this study are to describe the struggle of James J. Braddock viewed from Individual Psychological perspective, and to analyze the film Cinderella Man based on its structural elements. The research is conducted by using descriptive qualitative method. In this method, the researcher uses two data sources, namely primary and secondary data source. The Primary data is film Cinderella Man directed by Ron Howard. The secondary data Sources are the books about psychology and the other sources, which are related to the structural Analysis. The technique of collecting data is observation and literature review. The results of the study show that: firstly, the analysis of the structural element of the film shows a solid unity. Secondly, the psychological analysis shows that James.J.Braddock's character and the purpose of his life being a good father, makes better life, Safety for his family, comeback in professional boxer and the last motives are love, respect and family.